2016
DOI: 10.1371/journal.pone.0149266
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 5 Protects TGF-β Induced Fibrosis by Inhibiting Stat3 Activation in Rat Kidney Interstitial Fibroblast Cells

Abstract: Renal fibrosis is a common final pathway of end-stage kidney disease which is induced by aberrant accumulation of myofibroblasts. This process is triggered by reactive oxygen species (ROS) and proinflammatory cytokines generated by various source of injured kidney cells. Peroxiredoxin 5 (Prdx5) is a thiol-dependent peroxidase that reduces oxidative stress by catalyzing intramolecular disulfide bonds. Along with its antioxidant effects, expression level of Prdx5 also was involved in inflammatory regulation by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
5
23
0
Order By: Relevance
“…Furthermore, dysregulation of lncRNAs which contributes to overexpression of pro-inflammatory cytokines and overactivation of pro-inflammatory pathways are also largely implicated in the pathogenesis of inflammatory diseases, including cancers. 38 Revealing more inflammationrelated lncRNAs and their function, especially for maintaining chronic inflammation will be helpful for unveiling the pathogenic mechanisms of inflammatory disease. lncRNA -NEAT1 has been found to promote HCC by sponging microRNA, modulating abnormal lipolysis or affecting the epithelialmesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dysregulation of lncRNAs which contributes to overexpression of pro-inflammatory cytokines and overactivation of pro-inflammatory pathways are also largely implicated in the pathogenesis of inflammatory diseases, including cancers. 38 Revealing more inflammationrelated lncRNAs and their function, especially for maintaining chronic inflammation will be helpful for unveiling the pathogenic mechanisms of inflammatory disease. lncRNA -NEAT1 has been found to promote HCC by sponging microRNA, modulating abnormal lipolysis or affecting the epithelialmesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…1 Furthermore, we found that metformin targets the TGFβ1 downstream signalling pathway by directly interacting with TGFβ1 in an AMPK-independent manner. 26 Additionally, previous studies showed that metformin suppressed signal transducer and activator of transcription 3 (STAT3) activation, thereby decreasing the expression of multiple profibrotic genes in the kidney 28,29 via the AMPK-independent pathway. 27 Second, the protective effects observed in AMPKa2 −/− mice may be due to AMPKα1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…As a subtype of PDGF, PDGF-BB has a strong mitogenic effect on fibroblasts (Lin et al, 2015). TGF-β and PDGF-BB have usually been employed as the fibrosis models in previous studies for their fibrosis-promoting effect (Cho et al, 2016;Choi et al, 2016). The PDGF receptor (PDGFR) signal pathway is involved in both angiogenesis and fibrosis and has become a new target for treating fibrosis.…”
Section: Introductionmentioning
confidence: 99%